SOSIALISASI SEDIAAN KRIM EKSTRAK DAUN NANGKA (ARTOCARPUS HETEROPHYLLUS L.) TERHADAP BAKTERI PROPIONIBACTERIUM ACNE - Fahma Shufyani; Dewi Kartika; Jhon Patar Sinurat (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Jackfruit leaf is (Artocarpus heterophyllus L) is one of the natural ingredients that can be used as a therapeutic treatment of acne. To facilitate is use the extract is made in the form of a cream. This study aims to determine the antibacterial activity of anti-acne cream jackfruit leaf extract against propionibacterium acne with concentrations of 30%, 50%, 70%, and 90%. Compounds that act as antibacterials on jackfruit leaves include flavonoids, tannins, saponins. This research method is an ANOVA one way method. The extraction method used is the maceration method. The tests include physical stability test and anti-acne activity test. Physical preparation stability test is carried out every 6 days for 3 weeks. While the anti acne activity observation test was carried out on bacteria of Propionibacterium acne. Based on organoleptic observation got formulations 1 and 2 there was no change, while 3,4,5 there was a change. Anti acne activity test showed that formulations 1 and 2 were more effective than formulations 3, 4, 5 with average inhibition zone of 9,5 mm.